Short Video Media and Vocabulary Development in Young EFL Learners: Video Pendek dan Pengembangan Kosakata pada Pelajar Bahasa Inggris sebagai Bahasa Asing yang Masih Muda - Setiawan, Muhammad Ade; Fediyanto, Niko (Indonesian Journal of Education Methods Development, 2026)
General Background: Vocabulary mastery is a fundamental component of English language learning, particularly for young learners in multilingual and technology-driven educational contexts. Specific Background: The integration of short video platforms in classroom instruction has become increasingly common, offering multimodal input aligned with cognitive multimedia learning principles. Knowledge Gap: Despite growing interest in digital video use, limited empirical evidence addresses students’ perceptions and vocabulary development within structured short video–based instruction for young EFL learners. Aims: This study aims to examine students’ perceptions of short video use in vocabulary learning and to analyze its contribution to vocabulary development in an English as a Foreign Language classroom. Results: The findings indicate positive student responses toward the use of short videos, highlighting improved vocabulary recognition, contextual understanding, and learning engagement supported by quantitative data analysis. Novelty: The study provides context-specific empirical evidence on short video–mediated vocabulary instruction within young learner settings, integrating perception analysis and structured quantitative measurement. Implications: These results contribute to technology-integrated language pedagogy and offer practical guidance for English teachers seeking to incorporate short video media into vocabulary instruction. Keywords: Short Video Learning, Vocabulary Development, Young EFL Learners, Multimedia Instruction, Student Perception Key Findings Highlights Students demonstrated strong acceptance of video-based classroom activities. Quantitative data showed measurable gains in lexical recognition and contextual usage. Multimedia-supported instruction aligned with cognitive learning principles in classroom practice.